Educational attainment: a French-German comparison - Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 2001)
This documentation analyses the structure of educational attainment in France and Germany. While France and Germany share in many respects similar socioeconomic structures, they sharply differ with respect to their educational system. First, the three-tiered secondary school system in Germany, where pupils are streamed after primary schooling according to their learning ability into different secondary schools, contrasts with the situation in France, where all pupils attend a single structure up to upper secondary level. Moreover, in France, general education is more prized than vocational education. The French maturity certificate, has a key position in the educational system, while vocational education tends to be reserved to those pupils who have failed on the way to maturity completion. By contrast, the German education system is strongly oriented towards vocational training and the apprenticeship has a central position. At the higher education level, a relatively homogenous system in Germany can be opposed to a much more differentiated landscape in France, both in terms of types of institutions and of gradation of educational credentials.
Keywords: 330; Bildungsniveau; Bildungswesen; Vergleich; Deutschland; Frankreich